Kinetics of the Reaction of Semicarbazide With Some Tetrahydropyran-4-Ones - Varadachari, R.; Gurumurthy, R.; Mangalam, G.; Rajavel, G. (Asian Journal of Chemistry, 2010)
The rates of the reaction of semicarbazide with some substituted tetrahydropyran-4-ones have been measured at 40º,45º and 50º in 80% ethanol-water (v/v) at pH = 6.4. A large rate retardation is observed as the steric crowding about the carbonyl group increases indicating a rate limiting attack of the base on the carbonyl. The result throw light on the conformations of these compounds.